Varenicline Efficacy on Tobacco Dependence in Black/African Americans in the United States: A Systematic Review - Mansour, Charlene; DeJaco, Victoria; Ahlberg, Caitlyn; Schreiber, Raiza; Lansey, Dina G.; Minocha, Geeta; Khoury, Shireen; Kaplan, Bekir; Kaplan, Tugba; Jassal, Mandeep; et al. (Archives of Clinical and Biomedical Research, 2023)
Introduction: In 2018, the United States (US) achieved the lowest prevalence of active cigarette smoking since tracking began in 1965 at 13.8%. One factor that has influenced the decline in smoking is the advancement of pharmacotherapeutic treatments targeting the nicotine addiction component of tobacco dependence, specifically varenicline. However, it is unclear if the success of varenicline is evident in all diverse populations. We conducted a systematic review to evaluate the efficacy of varenicline based on race, specifically on Black/African Americans, with regards to smoking cessation. Methods: In this systematic review, the online databases PubMed, Embase, Web of Science, and Scopus were searched from 2000 through July 20, 2021. We report varenicline’s efficacy on smoking cessation and tobacco dependence in Black/African American individuals. Results: We identified three trials that recruited a majority of Black/ African American participants. In all three trials, varenicline was found to be effective and safe; however, abstinence rates varied by socioeconomic factors, genotyping, and adherence. Conclusion: Moving forward, over-representation in clinical trials should be a priority for marginalized patients, who are disproportionately impacted by the associated adverse outcomes of tobacco dependence. Understanding barriers to clinical implementation of evidence-based pharmacotherapy should also be prioritized.